2012
DOI: 10.1371/journal.pone.0042002
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography, Risk Factors and Genetic History of Hepatitis C Virus in Gabon, Central Africa

Abstract: BackgroundThe epidemiological and molecular characteristics of hepatitis C virus (HCV) infection in the general population have been poorly investigated in Africa. The aim of this study was to determine the prevalence, genotype distribution and epidemic history of HCV in the Gabonese general population.Methods/Principal FindingsA total of 4042 sera collected from adults in 220 villages in all nine administrative areas of the country were screened for antibodies to HCV. HCV NS5B region sequencing was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 51 publications
6
46
2
1
Order By: Relevance
“…In our study, the highest HCV prevalence was in 31-to 40-and 51-to 60-year-old individuals. This is similar to reports from Italy, central Africa, Japan and China, in which the highest rate of HCV infection was found in patients older than 50 [4,29]. Contrary to our study, the highest HCV prevalence in western Croatia was found in 21-to 30-yearold symptomatic individuals (44%, n = 76).…”
Section: Discussionsupporting
confidence: 85%
“…In our study, the highest HCV prevalence was in 31-to 40-and 51-to 60-year-old individuals. This is similar to reports from Italy, central Africa, Japan and China, in which the highest rate of HCV infection was found in patients older than 50 [4,29]. Contrary to our study, the highest HCV prevalence in western Croatia was found in 21-to 30-yearold symptomatic individuals (44%, n = 76).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the endemic subtypes of HCV genotypes 1, 2, and 4 have been found mainly in populations in geographically restricted areas in the sub-Saharan Africa or among African descendants in other geographic regions, but showing persistence for fewer centuries than that we here estimated for those novel Hainan variants [2629]. The best example of such can be seen in a recent report that has shown the existence of multiple HCV-2 “migrant clusters” moved at some point in the past from West Africa to the other parts of the world.…”
Section: Discussionmentioning
confidence: 67%
“…Genotype 3a is the second most common genotype in Europe after genotype 1 4,6 . Genotype 4 is prevalent in the Middle East [12][13][14] and in Central Africa [15][16][17] , while genotype 5 is common in South Africa 1,18 , and genotype 6 is found mainly in South Asia [19][20][21] . Genotype 7 has been found in Vietnamese patients with chronic hepatitis C, although some authors have advocated that it should be reclassifi ed as a subtype of genotype 6 22 .…”
Section: Introductionmentioning
confidence: 99%